(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Foot-and-mouth disease (FMD) is considered an economically devastating and highly contagious disease affecting both domestic and wild cloven-hoofed animals. It also poses a significant threat to the livestock industry in Bangladesh, impacting production and hindering trade. To address this concern, a study was conducted at Dhanbari Upazila, Tangail, Bangladesh, from October 5, 2022, to November 4, 2023. A total of 1071 cattle were examined, comprising 358 males and 713 females. The overall prevalence of FMD in Dhanbari Upazila was found to be 30.25%. The study investigated the influence of several factors, such as age, sex, breed, season, farming system, and vaccination, on the prevalence of FMD. Results indicated a significantly higher prevalence during winter (41.56%), with older cattle exhibiting a higher susceptibility (30.07%). Moreover, females were more susceptible (39.69%) than males (11.45%). The indigenous breeds were more prevalent (47.64%) than crossbreeds (19.76%). Additionally, a higher prevalence was found in non-vaccinated cattle (38.53%) than in vaccinated cattle (4.9%). Cattle from rural household farms have a higher prevalence (31.26%) compared to cattle from intensive farms (29.06%). Age, sex, breed, season, vaccination, and nutrition were significantly (p<0.05) associated with the prevalence of FMD. These findings highlight the genetic factors, managemental factors, and seasonal variations that contribute to the prevalence of FMD in this area. Moreover, it would help the farmers to establish an effective prevention and control program for FMD. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 295-303